116k views
5 votes
Algebra help pls y'all <3

Algebra help pls y'all <3-example-1

2 Answers

3 votes
f(2)=6
f(6)=58

change=52

it increases by 13 times
User Xierui
by
5.9k points
3 votes
Substitute in 2 for x in the equation:

f(2) = 2^2 + 5(2) - 8

= 4 + 10 - 8

= 6

Then, substitute in 6 for x in the equation:

f(6) = 6^2 + 5(6) - 8

f(6) = 36 + 30 - 8

= 58

To find the average rate of change, take the values you got from substituting the x-values in from above, then divide by the difference of the x-values:

(f(6) - f(2)) / (6-2)

= (58-6) / (6-2)

= 52/4

= 13
User Rendon
by
6.2k points